2023
DOI: 10.1021/acsomega.3c02688
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Ball Mill Performance in Recycled Ultrafine Graphite Waste Production for Carbon Block Applications

Waroot Kanlayakan,
Siraprapa Lhosupasirirat,
Chonradee Amnatsin
et al.

Abstract: A carbon block is a carbonaceous material used in various applications such as bearings, mechanical seals, and electrical brushes. This work aims to fabricate carbon blocks from industrial graphite waste, a residue from the cutting and tooling process of graphite block production. The ball milling process was used to fabricate ultrafine graphite waste to enhance the packing of carbon blocks. The milling performance was profoundly affected by dispersing agents in which sodium dodecyl sulfate (SDS), lignosulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…To avoid the viscosity build-up, chemical additives such as surfactants have been used for lowering the viscosity during milling. In this experiment, a sufficient amount of surfactants was used to control viscosity. ,, The slurry viscosity process from both the bead and ball milling processes, as shown in Figure , revealed an increase in the viscosity as the milling time increased. The results revealed an exponentially improving rate of viscosity in bead milling and a linear increase in the ball milling process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid the viscosity build-up, chemical additives such as surfactants have been used for lowering the viscosity during milling. In this experiment, a sufficient amount of surfactants was used to control viscosity. ,, The slurry viscosity process from both the bead and ball milling processes, as shown in Figure , revealed an increase in the viscosity as the milling time increased. The results revealed an exponentially improving rate of viscosity in bead milling and a linear increase in the ball milling process.…”
Section: Resultsmentioning
confidence: 99%
“…A surfactant helps control viscosity build-up during the milling process due to an increase in the total surface area of the particle by preventing milled graphite particles from reagglomeration. Our previous publication 40 emphasized the effect of surfactants (SDS, LS, and LS-SDS) on the ball milling performance for the preparation of ultrafine graphite scrap production from graphite waste and found that mixed surfactants (LS-SDS) provided better milling efficiency as well as better control of slurry viscosity build-up during ultrafine graphite production. An anionic surfactant (SDS) provides electrostatic stabilization for the ground slurry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 The Raman spectra of G and TG powders shown in whereas the 2D band became thinner and broader due to the graphite treatment and the deformation of the graphite structure. 37 According to the research conducted by Kanlayakan et al, 38 broken bonds result in a significant number of defects at the edges of graphite particles.…”
Section: Morphological and Structural Characterization Of G And Tg Po...mentioning
confidence: 99%
“…This, in turn, can amplify the imperfections caused by the edge effect of the graphene layers. 38 The stress induced on the TG particles also affects the number of crystal defects. The I D /I G ratio has increased, possibly due to the partial exfoliation and fragmentation of graphite particles into smaller particles with fewer graphene layers.…”
Section: Morphological and Structural Characterization Of G And Tg Po...mentioning
confidence: 99%